Respuesta :

Given:

Polynomial [tex]x^2+6x+20[/tex]

To find:

The equivalent polynomial.

Solution:

[tex]x^2+6x+20=0[/tex]

a = 1, b = 6, c = 20

Using quadratic formula:

[tex]$x=\frac{-b \pm \sqrt{b^{2}-4 a c}}{2 a}[/tex]

[tex]$x=\frac{-6 \pm \sqrt{6^{2}-4 \cdot 1 \cdot 20}}{2 \cdot 1}[/tex]

[tex]$x=\frac {-6 \pm \sqrt{-44}}{2}[/tex]

44 can be written as 11 × 4 = 11 × 2²

[tex]$x= \frac {-6 \pm \sqrt{-11 \times 2^2}}{2}[/tex]

[tex]$x= \frac {-6 \pm2 \sqrt{-11 }}{2}[/tex]

[tex]$x =\frac{2(-3 \pm i \sqrt{11})}{2}[/tex]

Cancel the common factor 2.

[tex]$x =-3 \pm i \sqrt{11}[/tex]

[tex]$x =-3 + i \sqrt{11}[/tex],   [tex]$x =-3 - i \sqrt{11}[/tex]

Convert into factors.

[tex]$x -(-3 + i \sqrt{11})=0[/tex], [tex]$x -(-3 - i \sqrt{11})=0[/tex]

[tex]$x + (3 - i \sqrt{11})=0[/tex], [tex]$x + (3 + i \sqrt{11})=0[/tex]

[tex]$(x + (3 - i \sqrt{11}))(x + (3 + i \sqrt{11}))[/tex]

Interchange their positions.

[tex]$(x + (3 + i \sqrt{11}))(x + (3 - i \sqrt{11}))[/tex]

Therefore option B is the correct answer.

The equivalent polynomial is [tex]$(x + (3 + i \sqrt{11}))(x + (3 - i \sqrt{11}))[/tex].